Assistance given to the “carriedmasculinebeing” of the HPV: contributions of nursing - Arcoverde, Marcos A.M.; Wall, Marilene L. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: currently the infection for the HPV is considered one of the DST most frequent in the whole world. However, it is disrespected in theprevention between the men. The proposal of this work was to promote a study on the infection of the HPV directed to the masculine population. Objective: to know the assistance given, the “carrying masculine being” of the HPV and its relation with this illness, the diagnosis, the treatment, theprevention and the quality of life. Methods: one is about a qualitative research, whose referencial of analysis is based on the “analysis of the rela-tions”. Result: the quarrel of the results brought tona the inadequação of the assistance to the men, and some of its feelings front to the infection forthe HPV. Conclusion: necessity of reorganization of the strategies of health enters the considerações salient it, directing them it the assistance to thehealth of the man.